Molecular detection of Exserohilum turcicum, agent of northern corn leaf blight - Bunkoed, Warapon; Chaijuckam, Patcharavipa; Kasem, Supot; Chatnaparat, Tiyakhon; Prathuangwong, Sutruedee (Agriculture and Natural Resources, 2024)
Importance of the work: Exserohilum turcicum has a wide host range and high genetic variability in terms of its morphology, virulence and genetic structure. The recovered isolate varied considerably in morphology, including colony color, growth of pathogen, conidial structures, size and radical mycelial growth. Objectives: To design a species-specific primer for E. turcicum based on inter-simple sequence repeat (ISSR) markers for the detection of the presence of E. turcicum on corn leaves. Materials & Methods: Polymerase chain reaction analysis of 241 isolates of E. turcicum using ISSR molecular markers revealed only one primer, (ACC)5, a unique DNA fragment set with 4- consistent polymorphic bands that clearly distinguished all isolates from closely related fungi. A single-specific molecular marker was designed, targeting a portion from a selected fragment region. Results: The primer set amplified a product of 348 bp from all isolates of E. turcicum and did not amplify any DNA of other closely related fungi. In addition, the presence of the SEF/SER-Et41 gene region in the E. turcicum isolates was confirmed using dot blot analysis. Main finding: The specific SEF/SER-Et41 primer set could be used as a reliable diagnostic method and useful tool for epidermiological study for the sensitive and specific detection of E. turcicum.